Determination of the spin diffusion length in germanium by spin optical orientation and electrical spin injection. (22nd September 2016) - Rinaldi, C; Bertoli, S; Asa, M; Baldrati, L; Manzoni, C; Marangoni, M; Cerullo, G; Bianchi, M; Sordan, R; Bertacco, R; Cantoni, M
Abstract: The measurement of the spin diffusion length and/or lifetime in semiconductors is a key issue for the realisation of spintronic devices, exploiting the spin degree of freedom of carriers for storing and manipulating information. In this paper, we address such parameters in germanium (0 0 1) at room temperature (RT) by three different measurement methods. Exploiting optical spin orientation in the semiconductor and spin filtering across an insulating MgO barrier, the dependence of the resistivity on the spin of photo-excited carriers in Fe/MgO/Ge spin photodiodes (spin-PDs) was electrically detected. A spin diffusion length of 0.9  ±  0.2 µ m was obtained by fitting the photon energy dependence of the spin signal by a mathematical model. Electrical techniques, comprising non-local four-terminal and Hanle measurements performed on CoFeB/MgO/Ge lateral devices, led to spin diffusion lengths of 1.3  ±  0.2 µ m and 1.3  ±  0.08 µ m, respectively. Despite minor differences due to experimental details, the order of magnitude of the spin diffusion length is the same for the three techniques. Although standard electrical methods are the most employed in semiconductor spintronics for spin diffusion length measurements, here we demonstrate optical spin orientation as a viable alternative for the determination of the spin diffusion length in semiconductors allowing for optical spin orientation.